СПОРТ МАРКЕТИНГИНИ МОДЕЛЛАШТИРИШНИНГ АҲАМИЯТИ - Саматов, Ж.А. (SCIENCE and SOCIETY, 2019)
The article discusses the models of the combined effect of marketers on goods and services in marketing theory. The classic model is model 4p, and the most popular model for sports marketing is model 6p (product, price or price, location, promotion, shift, staff and process).